A Study of Zooplankton Community in Alwand River and Dam- Iraq - Nargs A.Akbar; Luay A. Ali (Zanco Journal of Pure and Applied Sciences, 2020)
This study was conductn the zooplankton community from eight selected sites in the Alwand Rivers and Alwand Dam .Monthly samples of water, zooplankton and phytoplankton were collected for the period from June 2018 to February 2019 .The results of physico-chemical properties of water showed that the Air temperature ranged from 9-47 °C while water temperature ranged from 8-35.7 °C, hydrogen ion concentration in most of studied period was alkaline side above 7 , it was ranged between 7.6 -8.26, Turbidity ranged from 5.98 to 317.6 NTU, dissolved oxygen from 1.5 mg.l-1 to 3.13 mg.l-1 and electrical onductivity from 918 to 1782 µs.cm¹. Regarding to zooplankton, 81 species belonging to Rotifera (70 species), Cladocera (6 species) and zcopopoda (4 species). Also total count of phytoplankton was ranged from 60000 to 145000 cells.l-1 while total count of zooplankton from 4566.758 to 32433.98 ind.m-3.